Socioeconomic Impact of Livestock Farming: A Case Study of Baitadi and Darchula Districts, Nepal - Chapagaee, Pawan; Kunwar, Adhiraj; Bist, Dipak Raj; Khatri, Lokendra (International Journal of Applied Sciences and Biotechnology, 2024)
Dairy is the oldest staple food, along with fruits and vegetables, for humans. This study investigated the socioeconomic factors influencing milk and dairy production in Baitadi and Darchula districts, Shailyashikhar municipality, and Dilasaini rural municipality, Nepal. Among the 5384 livestock farmers, 100 livestock farmers were randomly selected for the investigation. The findings demonstrated the existence of a subsistence agricultural system for livestock farming with small landholdings. There is a dominance of males over females in decision-making, and workload is common for females. There is a unique practice of management for milk produced during the first three weeks of lactation: 99% of people do not consume milk for 19.81±4.597 mean days; 96% of people do not sell milk; 53% do not sell ghee; 73% of parents refuse to give their kids cow's milk during the first three weeks of breastfeeding; and 16% do not consume ghee because of their tradition. There are various problems in livestock farming, i.e., feed management, low land holding, disease, cost of production, less government support, and lack credit. Feed management was ranked first, whereas lowland holding was ranked second. Worms are the most common disease causing organism seen in livestock in the study area because of the lack of access to improved and well-sanitized barns. Herbal plants are commonly used in disease management. Sociocultural factors directly affect livestock production. Different traditional beliefs, a lack of improved breeds, disease, and feed management have direct impacts on milk production. Int. J. Appl. Sci. Biotechnol. Vol 12(3): 166-179.